2000
DOI: 10.1038/sj.onc.1203821
|View full text |Cite
|
Sign up to set email alerts
|

Complex regulation of CDKs and G1 arrest during the granulocytic differentiation of human myeloblastic leukemia ML-1 cells

Abstract: We previously reported that all-trans retinoic acid (ATRA) and granulocyte-macrophage colony-stimulating factor (GM ± CSF) synergistically induced granulocytic dierentiation in human myeloblastic leukemia ML-1 cells. The combination of these agents also suppressed DNA-synthesis. In the present study, we investigated the suppression of cyclin dependent kinase (CDK) activities resulting in G1 arrest in dierentiated ML-1 cells. We show that treatment of ML-1 cells with ATRA plus GM-CSF results in G1 arrest and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The study by Hsieh et al (2000) measured cell cycle regulators in nontransformed murine proerythroblasts undergoing in vitro di erentiation in response to erythropoietin. The ®ndings of this study were largely consistent with those of Matushansky et al (2000b), as were changes observed in a myeloid di erentiation model (Shimizu et al, 2000). In contrast, Tamir noted a di erent pattern of interactions in the HB60-5 cell line, which grows in SCF plus erythropoietin and di erentiates upon removal of SCF (Figure 3b).…”
Section: Cell Cycle Regulators and Erythropoiesissupporting
confidence: 84%
“…The study by Hsieh et al (2000) measured cell cycle regulators in nontransformed murine proerythroblasts undergoing in vitro di erentiation in response to erythropoietin. The ®ndings of this study were largely consistent with those of Matushansky et al (2000b), as were changes observed in a myeloid di erentiation model (Shimizu et al, 2000). In contrast, Tamir noted a di erent pattern of interactions in the HB60-5 cell line, which grows in SCF plus erythropoietin and di erentiates upon removal of SCF (Figure 3b).…”
Section: Cell Cycle Regulators and Erythropoiesissupporting
confidence: 84%
“…In contrast to p27, these data showed increased p21 levels induced by Akt. The function of p21 in cell cycle is complex, and new evidence suggests that the main function during cell cycle progression appears to be ensuring appropriate cdk4 activation and cell survival (31)(32)(33)(34)(35). The role of p21 in the proliferative phenotype is unclear, but it is possible that the increase in the number cdk4 complex proteins (cyclin D1, D2, and p21) stabilizes and prevents p21 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…43 In contrast, p21 Cip1 can bind to and inhibit kinase activities of Cdk2/cyclin A and Cdk2/cyclin E complexes from the late G 1 until the S phase. 44,45 …”
Section: Cell Cycle Overviewmentioning
confidence: 99%